Diversity of Land and Freshwater Snail (Mollusca: Gastropoda) of Laiwangi Wanggameti National Park, Sumba Island, Indonesia - Mujiono, Nova; Isnaningsih, Nur Rohmatin (UIN Sunan Gunung Djati Bandung, 2021)
A study on the malacofauna of Laiwangi Wanggameti National Park (LWNP) in Sumba Island has been conducted. This study aims were to reveal the diversity of malacofauna in Sumba and compare it with those in the Lesser Sunda Islands. Observations were made on 20 stations using plots (10 x 10 m) in Wanggameti and Laiwangi. Specimens were collected for two hours in each plot. Twenty families and 44 species have been identified. The overall number of species from Sumba increased from 126 to 143 species. The LWNP represents 31% diversity of malacofauna in Sumba Island. Seventeen species are considered as new records for the island. Five endemic land snail species are still observed inside the park. The diversity and population density tend to be higher in Laiwangi area with lower altitudes than in Wanggameti area with higher altitudes. Two dominant species are Asperitas bimaensis cochlostyloides and Tarebia granifera. Species composition in Sumba is more similar to Bali compared with the other six neighboring islands.